Submicron-sized MoRe-doped Si-MoRe Josephson junctions with a low specific capacitance. (June 2020) - Kalenyuk, A; Shapovalov, A; Shnyrkov, V; Shaternik, V; Belogolovskii, M; Febvre, P; Schmidl, F; Seidel, P
Abstract: We start with a short look at the problem of low-capacitance Josephson junctions, its history, and actual state-of-the-art. It is argued that such devices are important for applications requiring nonhysteretic current-voltage characteristics since reduction of capacitance by several times makes it possible to increase the device resistance by the same amount while keeping the McCumber-Stewart damping parameter unaltered. Moreover, at very high frequencies the capacitance in the RCSJ circuit with a parallel connection starts to shunt the superconducting current component due to reduction of the corresponding reactance inversely proportional to C. Hence, to extend the operating frequency range of a Josephson junction its capacitance should be as small as possible. As a solution of a new type of the Josephson device, less resistive and with smaller capacitance, we propose and realize a submicron-sized trilayer with tens nm-thick Si interlayer doped by metallic ultra-small inclusions and superconducting Mo-Re alloy electrodes.